Crypto Assets and Regulatory Challenges in Business Finance - Sanyal, Chinhita (International Journal of Advances in Business and Management Research (IJABMR), 2025)
The advent of cryptocurrency assets has ushered in a new era in the financial markets, characterised by groundbreaking opportunities and unprecedented complexities in business finance. These digital assets, underpinned by blockchain technology, have introduced decentralised, secure, and efficient transaction mechanisms that challenge traditional financial systems. However, the rapid expansion of cryptocurrencies, decentralised finance (DeFi), and blockchain-based financial instruments has far outpaced the development of regulatory frameworks. This discrepancy has given rise to significant legal ambiguities, compliance hurdles, and financial risks that businesses and policymakers must navigate. This paper delves into the fundamental nature of crypto assets, their growing integration into corporate finance strategies, and the pressing regulatory dilemmas they present. It examines the challenges faced by financial institutions, corporations, and regulators, including jurisdictional conflicts, anti-money laundering (AML) compliance, market manipulation risks, and cybersecurity vulnerabilities. The discussion culminates in a proposed roadmap for achieving regulatory harmony and mitigating risks, emphasizing the need for global coordination, adaptive policymaking, and technological solutions such as artificial intelligence (AI) and blockchain analytics. By synthesising academic research, real-world case studies, and comparative regulatory analyses, this paper aims to provide a comprehensive understanding of the current landscape and future trajectory of crypto assets in business finance. The findings underscore the necessity of a balanced regulatory approach—one that fosters innovation while safeguarding financial stability and investor protection.